Science Laboratory Activities: A Profile of the Implementation and Constraints of Junior High School Natural Science Teachers - Adam Malik; Hasniah Aliah; Seni Susanti; Mujib Ubaidillah; Ramdani Wahyu Sururie (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
This study aims to describe the implementation and various obstacles of laboratory activities in junior high schools. The study employed the descriptive quantitative method. The subjects of the study were science teachers in 41 junior high schools representing 4 areas of the Natural Sciences Teachers' Consultative Assembly (MGMP IPA) in Jawa Barat Province. The instrument employed was a questionnaire. The technical analysis of the data was conducted by calculating the average percentage of each answer choice of each statement. This research reveals that 1) the students’ motivation for conducting laboratory activities is high; 2) the implementation of laboratory activities is conducted separately by employing theoretical classroom learning; 3) the source of guidance for laboratory activities is a model of cookbook laboratory; and 4) some obstacles in laboratory activities include insufficient laboratory spaces, less standardized and insufficient number of most equipment, the availability of manuals for laboratory activities, insufficient instructions to use laboratory equipment, and teachers’ difficulties in designing, implementing, and evaluating laboratory activities. It is concluded that in general teachers and students are very enthusiastic about conducting laboratory activities in science learning, but they still have several constraints, especially in the available infrastructures.